Assessing educational materials in primary and secondary schools. Four assessment models - Hansen, Hans Jørgen (Georg-Eckert-Institut für Internationale Schulbuchforschung, 2010)
What characterizes the quality of educational materials – and – how can educational materials be assessed? These questions are central not only in a pedagogical practice but also in research and in educational policy in general, nevertheless, this field seems only examined and discussed very rarely in a theoretical perspective. There is quite a number of models for analysing and assessing educational materials among educators, however, what they seem to have in common is a lack of a theoretical foundation in relation to the concept educational materials and in relation to assessment. Consequently there is an imminent need for a certain degree transparency and structure when assessing teaching materials. Assessment of teaching tools opens to a range of fundamental questions, which can be found in much evaluation theory: What is the evaluation's object? Which method are you to use in order to collect knowledge? What are the evaluation's criteria build on, and what is the evaluation to be used to?

Was bedeutet „Qualität” bei Lehr- und Lernmaterialien und wie können diese bewertet werden? Solche nicht nur für die pädagogische Praxis relevanten Fragestellungen sind bisher selten aus einer theoretischen Sichtweise untersucht und diskutiert wurden. Obwohl eine Reihe von Ansätzen zur Analyse und Bewertung von Lehr- und Lernmaterialien existiert, scheint den meisten dieser Ansätze die theoretische Fundierung in Bezug auf Konzept und Bewertung zu fehlen. Folerichtig besteht ein großer Bedarf nach Transparenz und Struktur bei der Bewertung von Lehr- und Lernmaterialien. Zahlreiche zentrale Fragestellungen der Evaluationstheorie finden sich auch bei der Bewertung dieser Materialien wieder: Was ist das Evaluationsobjekt? Welche Methoden werden zur Informationsgewinnung genutzt? Worauf beruhen die Evaluationskriterien, und wofür wird die Evaluation genutzt werden?
Kostenfreier Zugang. - Lizenz: creative commons: by-nc-nd
Keywords: Lehrmittel; Unterricht; Grundschule; Sekundarstufe